Uncertainty, responsibility, and the evolution of the physician/patient relationship - Henry, M. S. (Journal of medical ethics, 2006)
The practice of evidence based medicine has changed the role of the physician from information dispenser to gatherer and analyser. Studies and controlled trials that may contain unknown errors, or uncertainties, are the primary sources for evidence based decisions in medicine. These sources may be corrupted by a number of means, such as inaccurate statistical analysis, statistical manipulation, population bias, or relevance to the patient in question. Regardless of whether any of these inaccuracies are apparent, the uncertainty of their presence in physician information should be disclosed to the patient. These uncertainties are not, however, shared by physicians with patients, and have caused a direct increase in patient responsibilities and mistrust. Only when disclosure of uncertainty becomes commonplace in medical practice will the physician/patient relationship evolve to a level of greater understanding and satisfaction for both the physician and patient.